PROSES MANUFAKTUR MESIN PRESS KALENG MINUMAN BEKAS - Alif Putra Wicaksana (2022)
Used aluminum cans are objects that are used as water containers because of their resistance. However, discarded aluminum cans can become waste. Aluminum cans have a fairly high selling value, so that many used goods collectors collect the waste cans. Used aluminum cans have a large volume, so it becomes a problem in accommodating and transporting them to the recycling facility. A used beverage can press machine produced by a factory has a large design with a long manufacturing time and a high price. Based on this problem, the author made a press machine for used drink cans. The purpose of making this machine is to develop a more economical manufacturing process for used beverage can press machines so that it can be used by home industries. The machine made can press 26 cans/minute. The time required in the machining process of the used beverage can press machine is 4.52 hours and the tool fabrication cost is Rp 2.498.485 -.